2016
DOI: 10.1515/bioeth-2016-0005
|View full text |Cite
|
Sign up to set email alerts
|

Cellulases by Penicillium sp. in different culture conditions

Abstract: The high cost of cellulolytic enzymes used in the ethanol production process has led to a growing interest in situ production. The evaluation of the influence of several factors in the fungus Penicillium sp. cellulase production using pretreated sugarcane bagasse is very interesting. Penicillium sp. cellulase production by using filter paper as cellulosic substrate and the use of glucose, sucrose and lactose like co-substrates was assessed. In the experiments using filter paper as a cellulosic substrate, the h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 25 publications
(19 reference statements)
0
9
0
Order By: Relevance
“…This first analysis was carried out under the conditions described in Mesa (2010) [8] for the case of the application of two pretreatment stages to sugarcane bagasse and the configuration of enzymatic hydrolysis and fermentation separately. Enzymatic hydrolysis was carried out, as reported by Mesa et al (2016) [6] with an enzymatic load of cellulase of 10 FPU / g of pretreated substrate in dry base, 2.5% of surfactant based on dry fiber and 10% solids in the enzymatic hydrolysis. The enzymatic hydrolysis was carried out for 24 hours as well as the alcoholic fermentation.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This first analysis was carried out under the conditions described in Mesa (2010) [8] for the case of the application of two pretreatment stages to sugarcane bagasse and the configuration of enzymatic hydrolysis and fermentation separately. Enzymatic hydrolysis was carried out, as reported by Mesa et al (2016) [6] with an enzymatic load of cellulase of 10 FPU / g of pretreated substrate in dry base, 2.5% of surfactant based on dry fiber and 10% solids in the enzymatic hydrolysis. The enzymatic hydrolysis was carried out for 24 hours as well as the alcoholic fermentation.…”
Section: Methodsmentioning
confidence: 99%
“…Some of these byproducts present a great challenge for the chemical industry because they can be the raw material not only of ethanol but of several biodegradable compounds. Recirculation is a potential alternative to reduce the cost of enzymes, using their relatively high stability and high affinity for cellulose [6].The main difficulties to enzymatically hydrolyze lignocellulosic materials are related, on one hand, with the low specific activity of the enzymes currently available, and therefore with the need for a high consumption of them during the process, [7]. Among the advantages, it is known that enzymes are not consumed in the reactions that they catalyze; therefore, they are potentially recyclable.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…and for each type of sugarcane bagasse (natural and pre-treated with acid-alkaline and hydrogen peroxide solutions, as described in Salomão et al (2019)). The values of concentration and temperatures selected here were based on works found in the literature, which used agro-industrial residues to produce cellulases (Akinyele et al, 2014;Mesa et al, 2016;Jasani et al, 2016;Irfan et al, 2017;Fernandes et al, 2018). For these experiments, a 3 2 factorial design with two central points was used.…”
Section: Enzyme Production By Smfmentioning
confidence: 99%
“…With regard to Penicillium, it is possible to find very different values of cellulase production in the scientific literature, which depends on the species, culture medium and physical conditions used. Mesa et al (2016), in a study of culture medium optimization, obtained a production of 13 IU/L (CMCase) by a wild strain of Penicillium spp., with the addition of 1.5 g/L of sugarcane bagasse pretreated with acid-alkaline solution. Santa-Rosa et al (2018) found an activity of 600 IU/L by a strain of Penicillium spp.…”
Section: Production Of Cellulases By Fungimentioning
confidence: 99%